First-borns have greater BMI and are more likely to be overweight or obese: a study of sibling pairs among 26 812 Swedish women. Issue 1 (26th August 2015) - Derraik, José G B; Ahlsson, Fredrik; Lundgren, Maria; Jonsson, Björn; Cutfield, Wayne S
Abstract : Background: A number of large studies have shown phenotypic differences between first-borns and later-borns among adult men. In this study, we aimed to assess whether birth order was associated with height and BMI in a large cohort of Swedish women. Methods: Information was obtained from antenatal clinic records from the Swedish National Birth Register over 20 years (1991–2009). Maternal anthropometric data early in pregnancy (at approximately 10–12 weeks of gestation) were analysed on 13 406 pairs of sisters who were either first-born or second-born (n=26 812). Results: Early in pregnancy, first-born women were of BMI that was 0.57 kg/m 2 (2.4%) greater than their second-born sisters (p<0.0001). In addition, first-borns had greater odds of being overweight (OR 1.29; p<0.0001) or obese (OR 1.40; p<0.0001) than second-borns. First-borns were also negligibly taller (+1.2 mm) than their second-born sisters. Of note, there was a considerable increase in BMI over the 18-year period covered by this study, with an increment of 0.11 kg/m 2 per year (p<0.0001). Conclusions: Our study corroborates other large studies on men, and the steady reduction in family size may contribute to the observed increase in adult BMI worldwide.